Preparation method of high-viscosity polyvinylpyrrolidone-based gel electrolyte and application of high-viscosity polyvinylpyrrolidone-based gel electrolyte in aqueous zinc-iodine battery

By preparing a strong sticky polyethylene pyriricone -based gel electrolyte, the problem of zinc negative branches and side reactions in the zinc iodine battery in the water system, as well as the problem of many iodine ion shuttle effects, realizes the improvement of battery performance, including improving electrolytes and electrical electrodes The interface stability and zinc ion deposition uniformity.

CN119350678AActive Publication Date: 2025-01-24CHINA JILIANG UNIV

Patent Information

Application Number
CN202411875064.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-24
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In practical applications, the problem of short circuit and lowering of Coulombic efficiency in zinc negative electrode secondary batteries in the water system has the problem of zinc negative electrode dendrites and side reactions, and the shuttle effect of iodine positive electrodes affects the long cycle performance.

Method used

Adopt a strong adhesive polyethylene pyriricone -based gel electrolyte, adding biomass sugars and cross -linked agents through a polymer agglutation reaction with the monomer to form a high mechanical intensity and strong adhesive electrolyte, and soak through the zinc salt solution to obtain Gel electrolyte.

Benefits of technology

This electrolyte can not only inhibit the shuttle effect of the positive and multi -iodine ions and the side reaction of the zinc negative electrode, improve the interface stability of the electrolyte and the electrode, but also improve the uniformity of zinc ion deposition and the long cycle performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350678A_ABST
    Figure CN119350678A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-viscosity polyvinylpyrrolidone-based gel electrolyte and application of the high-viscosity polyvinylpyrrolidone-based gel electrolyte in an aqueous zinc-iodine battery, and belongs to the technical field of batteries. Comprising the following steps: mixing vinyl pyrrolidone with a monomer, adding a solvent, fully stirring, and then adding a cross-linking agent and an initiator for copolymerization to obtain a polyvinylpyrrolidone-based copolymer; mixing the polyvinylpyrrolidone-based copolymer with biomass saccharides, pouring the mixture into a mold, and performing heating treatment to obtain a composite film; and soaking the composite membrane in a zinc salt solution to obtain the high-viscosity polyvinylpyrrolidone-based gel electrolyte. According to the preparation method, the high-viscosity polyvinylpyrrolidone-based gel electrolyte can be prepared, and the electrolyte has the advantages of being high in binding power and mechanical strength, environmentally friendly, low in cost and the like. The high-viscosity polyvinylpyrrolidone-based gel electrolyte can be used for preparing an aqueous zinc-iodine battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a preparation method of a highly viscous polyvinyl pyrrolidone-based gel electrolyte and application of the electrolyte in aqueous zinc-iodine batteries. Background Art

[0002] As the core support for the development of new energy, electrochemical energy storage technology can effectively solve the problems of randomness, intermittency, volatility and dispersion of green new energy such as solar energy, wind energy, geothermal energy and tidal energy, and is of great significance for the large-scale production and application of new energy power sources. Rechargeable aqueous zinc-iodine battery is a new type of secondary battery system, which mainly realizes energy storage and release through the "solid-liquid conversion" of active substances, that is, Zn 2+ Zn(-0.76Vvs.SHE,820mAh g -1 ) and I2 I - (0.54Vvs.SHE, 211mAh g -1 ), the reaction kinetics of this mechanism are fast, and the introduction of high ionic conductivity aqueous electrolyte not only further improves the electrochemical kinetics of the system, but also ensures the safety of the system. In addition, the active substances zinc and iodine are highly abundant and low in cost, making zinc-iodine batteries easy to prepare on a large scale. However, the current practical application of aqueous zinc-iodine secondary batteries is mainly limited by the following two factors: 1. Zinc negative electrode dendrites and side reactions cause battery short circuits and reduce battery coulombic efficiency; 2. The shuttle effect of multiple iodide ions at the iodine positive electrode significantly affects the long cycle performance of the battery.

[0003] In response to the above problems, scientific researchers have conducted a lot of research, but most of them focus on inhibiting the shuttle effect of polyiodide ions in the iodine positive electrode, while the regulatory effect on the deposition of the zinc negative electrode is limited. For example, CN107666015A discloses a zinc-iodine secondary battery with an aqueous electrolyte system and a preparation method thereof. The positive electrode of the patent uses ordinary carbon materials to inhibit the formation of polyiodides, and the negative electrode only polishes the electrode; for example, CN117430824A discloses a nitrogen-doped hollow MOF material and its preparation method and application. The patent does not optimize and modify the zinc negative electrode; for example, CN115693022A discloses a zinc-iodine battery separator based on a covalent organic framework and its preparation method and application, which also has limited effect on improving the uniformity of zinc ion deposition and inhibiting side reactions at the zinc negative electrode. Summary of the invention

[0004] In view of this, the present invention proposes a preparation method of a highly viscous polyvinyl pyrrolidone-based gel electrolyte and an application of the same in an aqueous zinc-iodine battery.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the purposes of the present invention is to provide a method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte, comprising the following steps:

[0007] The vinyl pyrrolidone and the monomer are mixed, a solvent is added and the mixture is stirred thoroughly, and then a crosslinking agent and an initiator are added to carry out copolymerization reaction to obtain a polyvinyl pyrrolidone-based copolymer;

[0008] The polyvinyl pyrrolidone-based copolymer is mixed with biomass sugars, poured into a mold and heated to obtain a composite film;

[0009] The composite film is immersed in a zinc salt solution to obtain a highly viscous polyvinyl pyrrolidone-based gel electrolyte.

[0010] The present invention uses vinyl pyrrolidone and monomer as raw materials to prepare a polyvinyl pyrrolidone-based copolymer, thereby improving the stability of polyvinyl pyrrolidone in aqueous solution and improving the mechanical strength of the electrolyte. Biomass sugars contain a large number of polar functional groups, such as hydroxyl, carboxyl, ether bond, amino, etc., which can give the polyvinyl pyrrolidone-based gel electrolyte a stronger bonding force. In addition, biomass sugars are natural polysaccharides extracted from natural organisms, and have the advantages of being green, low cost and biodegradable.

[0011] Further, the monomer includes one or more of styrene, vinyl chloride, vinyl alcohol, vinyl acetate, ethoxyethylene, ethylene glycol vinyl ether, cyclohexyl vinyl ether, 2-vinyl pyridine, vinyl ethylene carbonate, acrylamide, acrylic acid, methyl methacrylate, ethyl acrylate, acrylonitrile and maleic acid.

[0012] Furthermore, the crosslinking agent is one or more of N,N'-methylene acrylamide, N,N'-methylenebisacrylamide, epichlorohydrin, dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxide, diisopropyl hydroperoxide, divinyl benzene and diisocyanate.

[0013] Furthermore, the initiator is one or more of potassium persulfate, sodium perbromide, benzoyl peroxide, ammonium persulfate, lauroyl peroxide, azobisdimethylvaleronitrile, sodium azobiscyanovalerate, benzoyl, azobisisopropylimidazoline hydrochloride, azobiscyanovaleric acid, azobisisobutyronitrile and azobisisobutyramidine hydrochloride.

[0014] Furthermore, the biomass sugars include one or more of sodium alginate, sodium carboxymethyl cellulose, cellulose, chitosan, gum arabic, guar gum, starch, xanthan gum, agar, peach gum and cyclodextrin.

[0015] Furthermore, the zinc salt has a concentration of 0.05-10 mol / L, including one or more of zinc sulfate, zinc chloride, zinc perchlorate, zinc trifluoromethanesulfonate, zinc acetate, zinc tetrafluoroborate and zinc bis(trifluoromethylsulfonyl)imide.

[0016] Further, the molar ratio of vinyl pyrrolidone to monomer is (0.1-10):1; and / or

[0017] The amount of the cross-linking agent added is 0.1-1% of the mass of the monomer; and / or

[0018] The amount of the initiator added is 0.1-1% of the mass of the monomer; and / or

[0019] The copolymerization reaction conditions are: temperature 20-100°C, time 1-48h; and / or

[0020] The mass ratio of the polyvinyl pyrrolidone-based copolymer to the biomass sugar is (0.1-10):1; and / or

[0021] The heating treatment conditions are: temperature 80°C, time 2h; and / or

[0022] The soaking time is 1-48h.

[0023] The second object of the present invention is to provide a highly viscous polyvinyl pyrrolidone-based gel electrolyte obtained by the above-mentioned preparation method.

[0024] The third object of the present invention is to provide an aqueous zinc-iodine battery, comprising the highly viscous polyvinyl pyrrolidone-based gel electrolyte.

[0025] Since polyvinyl pyrrolidone can form a charge transfer complex with polyiodide ions, it can effectively inhibit the shuttle effect of polyiodide ions in the positive electrode. The small number of water molecules in the gel electrolyte can also inhibit the shuttle effect of polyiodide ions. The strong bonding force of the gel electrolyte improves the interfacial stability between the electrolyte and the positive electrode, which is beneficial to the shuttling of zinc ions and improves the performance of the battery. At the same time, since the number of water molecules in the gel electrolyte is small, the side reactions related to water in the zinc negative electrode can also be inhibited. The strong bonding force of the gel electrolyte improves the interfacial stability between the electrolyte and the zinc negative electrode, which is beneficial to the shuttling of zinc ions and improves the performance of the battery. The gel electrolyte can increase the zinc ion deposition overpotential, regulate the zinc ion flux, inhibit the two-dimensional diffusion of zinc ions, and improve the uniformity of zinc ion deposition at the negative electrode. That is to say, the polyvinyl pyrrolidone-based gel electrolyte prepared by the present invention can not only inhibit the shuttle effect of polyiodide ions in the positive electrode by forming a charge transfer complex and reducing the number of water molecules, but also improve the stability between the electrolyte and the positive electrode through the strong bonding force of the electrolyte. The prepared polyvinyl pyrrolidone-based gel electrolyte can not only inhibit the side reactions of the zinc negative electrode by reducing the number of water molecules and improve the stability between the electrolyte and the negative electrode through the strong bonding force of the electrolyte, but also increase the zinc ion deposition overpotential through the polymer, regulate the zinc ion flux, inhibit the two-dimensional diffusion of zinc ions, and improve the uniformity of zinc ion deposition at the negative electrode.

[0026] Compared with the prior art, the present invention has the following advantages and technical effects:

[0027] The invention provides a method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte, and applies the prepared gel electrolyte in an aqueous zinc-iodine battery, which has the following advantages: 1) the preparation method provided by the invention can obtain a polyvinyl pyrrolidone-based gel electrolyte with high mechanical strength, strong bonding force, environmental protection and low cost; 2) the polyvinyl pyrrolidone-based gel electrolyte prepared by the invention can not only inhibit the shuttle effect of positive electrode polyiodide ions, but also improve the stability between the electrolyte and the positive electrode; 3) the polyvinyl pyrrolidone-based gel electrolyte prepared by the invention can not only inhibit the side reaction of the zinc negative electrode, improve the stability between the electrolyte and the negative electrode, but also improve the uniformity of negative electrode zinc ion deposition. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0029] Figure 1 This is a physical picture of the highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 1;

[0030] Figure 2is a tensile strain curve of the highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 1;

[0031] Figure 3 This is a 180° peeling test diagram of the highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 1;

[0032] Figure 4 This is the SEM image of the zinc foil after 10 cycles of the symmetric battery in Application Example 1;

[0033] Figure 5 This is the long cycle performance diagram of the symmetrical battery in Application Example 2;

[0034] Figure 6 The second cycle charge-discharge curve of the aqueous zinc-iodine button battery in Application Example 3;

[0035] Figure 7 Schematic diagram of the long cycle performance of the aqueous zinc-iodine button battery in Application Example 3;

[0036] Figure 8 Schematic diagram of the long cycle performance of the aqueous zinc-iodine button battery in Comparative Example 1;

[0037] Fig. 9 Schematic diagram of the long cycle performance of the aqueous zinc-iodine button battery in Comparative Example 2. DETAILED DESCRIPTION

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0043] The present invention provides a method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte, comprising the following steps:

[0044] 1) mixing vinyl pyrrolidone with monomers, adding a solvent and stirring thoroughly, and then adding a crosslinking agent and an initiator to carry out copolymerization to obtain a polyvinyl pyrrolidone-based copolymer; the solvent can be water;

[0045] 2) mixing the polyvinyl pyrrolidone-based copolymer with biomass sugar, pouring the mixture into a mold and heating the mixture to obtain a composite film;

[0046] 3) Soaking the composite film in a zinc salt solution to obtain a highly viscous polyvinyl pyrrolidone-based gel electrolyte.

[0047] In some embodiments of the present invention, the monomer includes one or more of styrene, vinyl chloride, vinyl alcohol, vinyl acetate, ethoxyethylene, ethylene glycol vinyl ether, cyclohexyl vinyl ether, 2-vinyl pyridine, vinyl ethylene carbonate, acrylamide, acrylic acid, methyl methacrylate, ethyl acrylate, acrylonitrile and maleic acid. Exemplarily, in the following embodiments of the present invention, the monomer can be selected from acrylamide or acrylic acid.

[0048] In some embodiments of the present invention, the crosslinking agent is one or more of N,N'-methylene acrylamide, N,N'-methylene bis acrylamide, epichlorohydrin, diisopropyl peroxide, benzoyl peroxide, di-tert-butyl peroxide, diisopropyl hydroperoxide, divinyl benzene and diisocyanate. Exemplarily, in the following embodiments of the present invention, the crosslinking agent can be selected from N,N'-methylene acrylamide or epichlorohydrin.

[0049] In some embodiments of the present invention, the initiator is one or more of potassium persulfate, sodium perbromide, benzoyl peroxide, ammonium persulfate, lauroyl peroxide, azobisdimethylvaleronitrile, sodium azobiscyanovalerate, benzoyl, azobisisopropylimidazoline hydrochloride, azobiscyanovaleric acid, azobisisobutyronitrile and azobisisobutyramidine hydrochloride. Exemplarily, in the following embodiments of the present invention, the initiator can be selected from azobisisobutyronitrile or ammonium persulfate.

[0050] In some embodiments of the present invention, the biomass sugars include one or more of sodium alginate, sodium carboxymethyl cellulose, cellulose, chitosan, gum arabic, guar gum, starch, xanthan gum, agar, peach gum and cyclodextrin. Exemplarily, in the following embodiments of the present invention, the biomass sugars can be selected from sodium alginate or chitosan.

[0051] In some embodiments of the present invention, the zinc salt includes one or more of zinc sulfate, zinc chloride, zinc perchlorate, zinc trifluoromethanesulfonate, zinc acetate, zinc tetrafluoroborate and zinc bis(trifluoromethylsulfonyl)imide. Exemplarily, in the following embodiments of the present invention, the zinc salt can be selected from zinc sulfate or zinc perchlorate. The concentration of the zinc salt is 0.05-10 mol / L. Exemplarily, in the following embodiments of the present invention, the effect is verified by taking the zinc salt concentration of 2 mol / L as an example.

[0052] In some embodiments of the present invention, the molar ratio of vinyl pyrrolidone to monomer is (0.1-10):1. For example, in the following embodiments of the present invention, the molar ratio of vinyl pyrrolidone to monomer is 0.7:1.

[0053] In some embodiments of the present invention, the amount of the cross-linking agent added is 0.1-1% of the mass of the monomer. For example, in the following embodiments of the present invention, the amount of the cross-linking agent added is 0.14% of the mass of the monomer.

[0054] In some embodiments of the present invention, the amount of the initiator added is 0.1-1% of the mass of the monomer. For example, in the following embodiments of the present invention, the amount of the initiator added is 0.47% of the mass of the monomer.

[0055] In the following examples of the present invention, the conditions of the copolymerization reaction are: temperature 50° C., time 20 h.

[0056] In some embodiments of the present invention, the mass ratio of the polyvinyl pyrrolidone-based copolymer to the biomass sugar is (0.1-10):1. For example, in the following embodiments of the present invention, the mass ratio of the polyvinyl pyrrolidone-based copolymer to the biomass sugar is 1:1.

[0057] In the following examples of the present invention, the conditions of the heating treatment are: temperature 80° C., time 2 h.

[0058] In the following embodiments of the present invention, the soaking time is 1-48 hours. Exemplarily, in the following embodiments of the present invention, the soaking time is 24 hours as an example for effect verification.

[0059] A highly viscous polyvinyl pyrrolidone-based gel electrolyte can be prepared by the preparation method.

[0060] The prepared highly viscous polyvinyl pyrrolidone-based gel electrolyte can be used to prepare aqueous zinc-iodine batteries.

[0061] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0062] The raw materials used in the present invention are all purchased from the market.

[0063] The technical solution of the present invention is further illustrated by the following embodiments.

[0064] Example 1

[0065] A method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte comprises the following steps:

[0066] (1) 2.43 g of vinyl pyrrolidone and 2.44 g of acrylamide (the molar ratio of the two is 0.7:1) are mixed, 2 mL of water is added, and the mixture is stirred thoroughly to obtain a mixed solution; 0.64 mg of N,N'-methylene acrylamide and 2.16 mg of azobisisobutyronitrile are added to the mixed solution, and then the whole is poured into a glass mold and heated at 50°C for copolymerization reaction for 20 hours, and a solid is obtained by freeze drying, and then ground into powder to obtain a polyvinyl pyrrolidone-based copolymer powder;

[0067] (2) 0.1 g of polyvinyl pyrrolidone-based copolymer powder was mixed with 0.1 g of sodium alginate and dissolved in 100 mL of water, stirred for 2 h, introduced into a mold and heated at 80 °C for 2 h, and demolded to obtain a composite film;

[0068] (3) The composite film was immersed in a 2 mol / L zinc sulfate solution for 24 h to obtain a highly viscous polyvinyl pyrrolidone-based gel electrolyte.

[0069] Figure 1 This is a physical picture of the highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 1. It can be seen from the figure that the gel electrolyte is transparent and the words CJLU can be seen below.

[0070] Figure 2 This is a mechanical tensile test of the highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 1. It can be seen from the actual picture that the gel electrolyte can withstand a strong tensile force without breaking. According to the tensile strain curve, the gel electrolyte can withstand a stretching rate of 685%, and the corresponding tensile force is 0.15 Mpa, indicating that the gel electrolyte has high mechanical strength and strong toughness.

[0071] Figure 3This is a 180° peel test of the highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 1. As can be seen from the figure, the cross-section of the gel electrolyte is 20 mm, and the bonding force it can withstand is about 2.9 N. Therefore, its bonding strength is 145 N / m, indicating that the gel electrolyte has a strong bonding force.

[0072] Application Example 1

[0073] The highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 1 was combined with two circular zinc foils with a diameter of 14 mm and a thickness of 0.01 mm to form a symmetrical battery. -2 , surface capacity is 1 mAh cm -2 The zinc foil was cycled for 10 times under the conditions of , and then the zinc foil after the cycle was disassembled and taken out, and the deposition morphology of the zinc foil was studied using SEM.

[0074] Figure 4 This is the SEM image of the zinc foil after 10 cycles of the symmetric battery in Application Example 1. Figure 4 It can be seen that the surface of the zinc foil after the cycle is smooth and tidy, and no zinc dendrites are formed, which proves that the electrolyte prepared in Example 1 of the present invention can improve the uniformity of zinc ion deposition.

[0075] Application Example 2

[0076] The highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 1 was combined with two circular zinc foils with a diameter of 14 mm and a thickness of 0.01 mm to form a symmetrical battery. -2 , surface capacity is 1 mAh cm -2 Long cycle test was carried out under the conditions of

[0077] Figure 5 This is the long cycle performance diagram of the symmetrical battery in Application Example 2. It can be seen from the figure that the symmetrical battery has no short circuit phenomenon after 4000 cycles.

[0078] Example 2

[0079] A method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte comprises the following steps:

[0080] (1) 2.43 g of vinyl pyrrolidone and 2.27 g of acrylic acid (the molar ratio of the two is 0.7:1) are mixed, 2 mL of water is added, and the mixture is stirred thoroughly to obtain a mixed solution; 0.64 mg of epichlorohydrin and 2.16 mg of ammonium persulfate are added to the mixed solution, and then the whole is poured into a glass mold and heated at 50° C. for copolymerization reaction for 20 h, and a solid is obtained by freeze drying, and then ground into powder to obtain a polyvinyl pyrrolidone-based copolymer powder;

[0081] (2) 0.1 g of polyvinyl pyrrolidone-based copolymer powder was mixed with 0.1 g of chitosan and dissolved in 100 mL of water, stirred for 2 h, introduced into a mold and heated at 80 °C for 2 h, and demolded to obtain a composite film;

[0082] (3) The composite film was immersed in a 2 mol / L zinc perchlorate solution for 24 h to obtain a highly viscous polyvinyl pyrrolidone-based gel electrolyte.

[0083] Application Example 3

[0084] The highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 2 is used in an aqueous zinc-iodine battery, and the specific steps are as follows:

[0085] (1) Mix 1g of iodine and 1g of activated carbon material in a sealed container, heat at 120°C for 2h, and cool to room temperature to obtain a carbon-iodine complex, which is used as the positive active material of the zinc-iodine battery;

[0086] (2) 0.7 g of carbon iodine complex, 0.15 g of carbon black conductive agent and 0.15 g of PVDF binder were mixed in N-methyl-2-pyrrolidone (NMP), ultrasonically dispersed to form a slurry, and evenly coated on a 0.05 mm thick titanium foil with a coating thickness of 150 μm. After vacuum drying, the slurry was cut into 12 mm diameter discs as positive electrode sheets;

[0087] (3) A circular zinc foil with a diameter of 14 mm and a thickness of 0.01 mm is used as the negative electrode;

[0088] (4) The positive electrode sheet, the negative electrode sheet and the highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared in Example 2 were assembled into an aqueous zinc-iodine button cell. The cell was -1 Cycling at current density, the charge and discharge cut-off voltage is 0.6-1.6Vvs.Zn 2+ / Zn.

[0089] Figure 6 This is the second cycle charge-discharge curve of the aqueous zinc-iodine button battery in Application Example 3. The charge-discharge platform is a typical platform for the active substance iodine. Figure 6 It can be seen that the average discharge voltage of the battery is about 1.2 V and the discharge capacity is 127 mAh g -1 , the charge capacity is 126.5 mAh g -1 , the coulombic efficiency is 99.6%, indicating that the battery has good cycle reversibility.

[0090] Figure 7 This is a schematic diagram of the long cycle performance of the aqueous zinc-iodine button battery in Application Example 3. It can be seen from the figure that at 1 Ag -1 The first cycle discharge capacity is 130.6 mAh g-1 (Based on the mass of the positive electrode active material), the first cycle coulombic efficiency is 96.8%, and the capacity retention rate after 2000 cycles is 88.1%, showing good long-cycle performance. -1 At a current density of , it takes about 5 minutes for the whole battery to charge and discharge once, showing good reaction kinetics.

[0091] Comparative Example 1

[0092] Same as Example 2, except that no acrylic acid monomer is added for copolymerization.

[0093] Figure 8 Schematic diagram of the long cycle performance of the aqueous zinc-iodine button battery in Comparative Example 1, which is the same as Application Example 3, except that the gel electrolyte prepared in Comparative Example 1 is used. It is found that at 1 A g -1 The first cycle discharge capacity is 120.9 mAhg -1 The first cycle coulombic efficiency is 95% (based on the mass of the positive electrode active material). After 979 cycles, the coulombic efficiency of the battery drops significantly, which means that the battery is short-circuited. The lack of copolymerization of other monomers significantly reduces the mechanical strength of the electrolyte, which cannot inhibit the growth of dendrites, resulting in a short circuit in the battery.

[0094] Comparative Example 2

[0095] Same as Example 2, except that the mixture is not mixed with chitosan.

[0096] Fig. 9 Schematic diagram of the long cycle performance of the aqueous zinc-iodine button battery in Comparative Example 2, which is the same as Application Example 3, except that the gel electrolyte prepared in Comparative Example 2 is used. It is found that at 1 A g -1 The first cycle discharge capacity is 121.7 mAh g -1 (based on the mass of the positive electrode active material), the first cycle coulomb efficiency is 95.3%, and after 2000 cycles, the discharge capacity is 68.6 mAh g -1 The capacity retention rate is 56.4%. The lack of biomass sugars reduces the bonding performance of the electrolyte, which is not conducive to the contact stability between the electrolyte and the electrode sheet, and reduces the cycle stability of the battery.

[0097] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte, characterized in that: The following steps are involved: The vinyl pyrrolidone and the monomer are mixed, a solvent is added and the mixture is stirred thoroughly, and then a crosslinking agent and an initiator are added to carry out copolymerization reaction to obtain a polyvinyl pyrrolidone-based copolymer; The polyvinyl pyrrolidone-based copolymer is mixed with biomass sugars, poured into a mold and heated to obtain a composite film; The composite film is immersed in a zinc salt solution to obtain a highly viscous polyvinyl pyrrolidone-based gel electrolyte.

2. The method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte according to claim 1, characterized in that: The monomers include one or more of styrene, vinyl chloride, vinyl alcohol, vinyl acetate, ethoxyethylene, ethylene glycol vinyl ether, cyclohexyl vinyl ether, 2-vinyl pyridine, vinyl ethylene carbonate, acrylamide, acrylic acid, methyl methacrylate, ethyl acrylate, acrylonitrile and maleic acid.

3. The method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte according to claim 1, characterized in that: The crosslinking agent is one or more of N,N'-methylene acrylamide, N,N'-methylene bis acrylamide, epichlorohydrin, diisopropyl peroxide, benzoyl peroxide, di-tert-butyl peroxide, diisopropyl hydroperoxide, divinyl benzene and diisocyanate.

4. The method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte according to claim 1, characterized in that: The initiator is one or more of potassium persulfate, sodium perbromide, benzoyl peroxide, ammonium persulfate, lauroyl peroxide, azobisdimethylvaleronitrile, sodium azobiscyanovalerate, benzoyl, azobisisopropylimidazoline hydrochloride, azobiscyanovaleric acid, azobisisobutyronitrile and azobisisobutyramidine hydrochloride.

5. The method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte according to claim 1, characterized in that: The biomass sugars include one or more of sodium alginate, sodium carboxymethyl cellulose, cellulose, chitosan, gum arabic, guar gum, starch, xanthan gum, agar, peach gum and cyclodextrin.

6. The method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte according to claim 1, characterized in that: The zinc salt has a concentration of 0.05-10 mol / L and includes one or more of zinc sulfate, zinc chloride, zinc perchlorate, zinc trifluoromethanesulfonate, zinc acetate, zinc tetrafluoroborate and zinc bis(trifluoromethylsulfonyl)imide.

7. The method for preparing a highly viscous polyvinyl pyrrolidone-based gel electrolyte according to claim 1, characterized in that: The molar ratio of vinyl pyrrolidone to monomer is (0.1-10):1; and / or The amount of the cross-linking agent added is 0.1-1% of the mass of the monomer; and / or The amount of the initiator added is 0.1-1% of the mass of the monomer; and / or The copolymerization reaction conditions are: temperature 20-100°C, time 1-48h; and / or The mass ratio of the polyvinyl pyrrolidone-based copolymer to the biomass sugar is (0.1-10):1; and / or The soaking time is 1-48h.

8. A highly viscous polyvinyl pyrrolidone-based gel electrolyte prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the highly viscous polyvinyl pyrrolidone-based gel electrolyte as claimed in claim 8 in aqueous zinc-iodine batteries.

Citation Information

Patent Citations

  • Water-phase electrolyte system zinc iodine secondary battery and preparation method thereof

    CN107666015A

  • Zinc-iodine battery diaphragm based on covalent organic framework as well as preparation method and application of zinc-iodine battery diaphragm

    CN115693022A

  • Nitrogen-doped hollow MOF material as well as preparation method and application thereof

    CN117430824A

  • Poly N-vinyl pyrrolidone-contained amphiphilic copolymer grafted by natural high polymer or water-solubility derivative thereof and preparation method thereof

    CN101643531A

  • Improvement on method for preparing complex of polyvinylpyrrolidone grafted with natural polymer or water-soluble derivate thereof and iodine derivate

    CN102002132A

Cited By

  • Hydrogel electrolyte modified by strong polar group as well as preparation method and application of hydrogel electrolyte

    CN120637633A

  • A strong polar group modified hydrogel electrolyte and a preparation method and application thereof

    CN120637633B